Non-targeted Metabolomics Analysis Based on LC–MS to Assess the Effects of Different Cold Exposure Times on Piglets - Chen, Yong; Ji, Hong; Guo, Jingru; Chen, Yan; Li, Wenjie; Wang, Shengping; Zhen, Li (Frontiers in Physiology, 2022)
Pigs are susceptible to low temperature conditions. Cold stress causes body metabolic changes to increase heat production to adapt to the adverse environment. To characterize and validate different metabolites in piglet liver at different exposure times, sixteen 30-day-old male weaned piglets with similar weights were randomly divided into four groups: the normal temperature group (24±2 °C, NT) and the cold exposure (4±2 °C) 2-hour group (CS2), 6-hour group (CS6) and 12-hour group (CS12). At the end of the experiment, the piglets were slaughtered, and the liver samples were analyzed using systemic nontargeted metabolomics. In positive and negative ion modes, there were 8 known differentially abundant metabolites (farnesyl pyrophosphate, isocitrate, triethanolamine, Phenylethylamine, deoxynosine, citric acid, maltotriose and epinephrine) between the CS groups and the control group. The 8 main differentially abundant metabolites involved in 7 metabolite classifications. Metabolic pathway and enrichment analyses revealed that the pathways involved 3 KEGG pathway classifications and most of the pathways were related to amino acid or energy metabolism, and the metabolic pathways were not identical to different cold exposure time. The metabolic pathways following 2h and 6h cold exposure were more related to carbohydrates and energy production, and metabolic pathways of 12h cold exposure were more related to the metabolism connected with epinephrine. Under different cold exposure time, the metabolite profiles showed different, and the metabolic pathways are also not the same.